Análise de sistemas de medição de desempenho na construção civil: oportunidades de melhoria a partir da literatura e da experiência de construtoras cearenses - Cândido, Luis Felipe (2015)
The growing debate on measuring performance among professionals and researchers from organizational management is still not enough to consolidate the measurement practices in the construction industry. Thus, this study aims to identify the opportunities for improvement of the Performance Measurement Systems (PMS) in construction management. To do so, an analyze of the performance measurement literature was carried out from disciplines as accounting, strategy, human resources, production and operations management, marketing and organizational behavior. This analysis provides a proposition of an audit tool to evaluate the PMS in Construction Companies. The proposed tool was validated by expert researchers with great experience with the PMS theme. The audit tool was used to analyze 22 models identified in the specific literature of PMS in construction over the last 25 years, which provided a mapping of the key features, roles and processes of measurement practices in that industry. This diagnostic use quantitative techniques and explore in depth the qualitative aspects, identifying gaps and opportunities of improvement. After the theoretical study, a multiple case study was carried out in three construction companies from Ceará, northeast of Brazil. As results of the case studies, an analyzing of the PMS of the companies was carried out. Moreover, propositions of improvements for the PMS were carried out and the audit tool was applied. In following, a matrix that correlates the roles and the processes of a PMS was formulated based in the experience of the same experts that validated the audit tool. With experience acquired, a framework that presents a holistic view of the measurement process was proposed, emphasizing the difference between indicators system and performance measurement system. This framework classify the PMS based on the audit tool and the matrix that correlates the roles and the processes of a PMS. The classification enable that construction companies evaluates if their PMS are able to support the uses to which they were designated. As conclusion, despite of the great number of initiatives to improve the PMS in Construction that were analyzed, the sector need to models of PMS that containing more scathing operational guidelines. If the evolution of PMS in Building Construction it is slow, as pointed out in literature, some evidences that confirm this thesis were mapped that enable propositions of improvement by academics and professionals. A research agenda was suggested, from the gaps and improvement opportunities found.